Developing countries and external debt: What is wrong? - Felipe, Jesus (Animo Repository, 2024)
LAST DECEMBER, the World Bank published its annual report on international debt (https://www.worldbank.org/en/programs/debt-statistics/idr/products). The report indicates that, in 2022, the developing countries spent $443 billion on debt-service repayment (principal plus interest) of their external public and publicly guaranteed debt, 5% more than in 2021. These payments are expected to rise in 2023 and 2024 due to the increase in interest rates. The report indicates that debt levels and high interest rates have set many countries on a path to crisis.